Analytical, Experimental, and Finite Element Analysis of Buckling and Wrinkling Failure Modes in Carbon/PVC Sandwich Panels - Günther Neto, João Alberto; Fuga, Felipe Ruivo; Medeiros, Ricardo de (Journal of Composites and Biodegradable Polymers, 2025)
Carbon fibre–reinforced PVC foam sandwich composites are widely used in aeronautical and marine structures due to their high strength-to-weight ratio. However, the stiffness mismatch between face sheets and cores may lead to local buckling modes such as face wrinkling and shear crimping when subjected to compressive loads. Therefore, this study presents a comprehensive investigation on the interaction between global and local buckling modes for sandwich beam structures with lengths varying between 45 and 500 mm subjected to compressive loads, through the comparison of analytical and finite element models using Abaqus® software. Analytical results show a critical force of 3481.1 N and 4017.5N for face sheet wrinkling and shear crimping, respectively. Numerical predictions for both phenomena present a maximum error of approximately 1%, showing that local buckling can be predicted independently of the slenderness ratio of the beam, as suggested by the analytical formulation. However, even for slender beams, the critical buckling load showed a coupling to local behaviour, reducing the corresponding eigenvalue. A maximum deviation of approximately 8% was obtained between analytical and numerical predictions. Finally, an experimental procedure was carried out to observe the associated buckling shapes. As indicated by analytical and numerical predictions, the specimen displayed a local buckling failure mechanism, however, at a much smaller load value related to geometric imperfections and asymmetric boundary conditions. Therefore, the study establishes a validation between analytical and numerical frameworks for predicting local instability failures in CFRP/PVC sandwich structures, providing a tool for engineers to the design of sandwich panels for enhanced structural performance and lightweight and safe components.